Unintended Consequences of Gender Equality Promotion in Swedish Multicultural Contraceptive Counseling: A Discourse Analysis. (August 2017) - Arousell, Jonna; Carlbom, Aje; Johnsdotter, Sara; Larsson, Elin C.; Essén, Birgitta
In this article, we explore how reproductive health care providers in Sweden, a country often described as one of the most gender-equal countries in the world, incorporate gender equality ideals in multicultural contraceptive counseling. In the tension between gender equality promotion on one hand and respect for cultural diversity and individualized care on the other, we will demonstrate that values of gender equality were often given priority. This is not necessarily undesirable. Nevertheless, our proposal is that the gender equality ideology may inhibit providers' ability to think differently about issues at stake in contraceptive counseling, which may negatively influence women's possibilities to obtain adequate support. At the end of the article, we suggest how health care providers' reflexivity might be used as a working tool for increased awareness about the taken-for-granted cultural norms that exist in their clinical milieu.